The Evaluation Metro Map - Sebastian Lemire (The Evaluation Center at Western Michigan University, 2024)
Background: The practice and profession of evaluation continue to evolve. Over the years, evaluation scholars and practitioners have developed a broad-and still broadening-range of evaluation approaches. These evaluation approaches are often combined with various study designs in real-world evaluations. To provide an overview of these approaches and designs, and inspired by my son's love of metro trains, I created an evaluation metro map.    Purpose: The purpose of this article is to describe the background, purpose, and benefits and limitations of the evaluation metro map. Setting: Not applicable Intervention: Not applicable Research Design: Not applicable Data Collection and Analysis: Not applicable Findings: Not applicable Keywords: